Gondolatok a hatóság indokolási kötelezettségéről Martonyi János az államigazgatási aktusok indokolása c. művének nyomán - Csatlós Erzsébet; Martonyi János (2023)
Times change and legal acts change, but to what extent do basic legal institutions and legal requirements change? In connection with the justification of official decisions, which are the values of the past that are timeless and worth going back to and saving, and which are necessarily doomed to change? Does the justification of authority decisions become simplified over time and as a result of development? These questions arose in connection with the 1971 study examined on the occasion of the Martonyi Memorial Conference. For this purpose, the study explored the legal background and international context in which János Martonyi summarized his thoughts, to what extent his contemporaries shared this, and then what stages the current regulatory environment has gone through since then. Taking a brief look at a few emerging issues, it can be seen that the obligation to provide reasons for authority decisions is by no means a closed topic, and the legal literature born several decades ago can still teach the legal practitioner a lesson. As a general, uniformly applied legal interpretation in practice, the Curia refers to the fact that the lack of justification (deficiency and/or inconsistency) is a serious violation of procedural law that cannot be remedied in the lawsuit, which renders the examined decision unfit for substantive examination, so the authority’s responsibility for properly justifying the decision can be said to be the same as in the age of Martonyi. The legislative environment has not changed significantly in terms of what the authority can rely on when fulfilling its obligations or it may have become more complicated if we only consider the emergence of data protection. However, when interpreting qualitative and quantitative issues within the framework of fundamental law, international law, and EU law, it can be seen that Martonyi’s ideas laid down in 1971 are timeless and can still be cited as a guide for interpretation. As said by Martonyi, a good justification is necessarily substantive, but at the same time short, devoid of any wordiness, and all these requirements are infringed if a formal, templated text is attached to the decision. The purpose of the resasoning is to present not only the mere result of bringing the facts under abstract legislation, but also to demonstrate the entire process of decision-making to justify the correctness of the decision to the parties, and even to have a reassuring and convincing effect on them to achieve implementation. At the same time, it justifies the validity of the decision, because it encourages the proceedingauthority to act with increased care both when discovering the facts and when selecting and interpreting the applicable legislation, so it also functions as a kind of self-control against the authority’s arbitrariness. Such insight in the decision-making process enables the review of the decision by those organs and bodies whose empowered to practice controll over the functioning of administration. Therefore, keeping the Martonyi premises in mind when interpreting legal paraphrases and balancing conflicting values still can show the direction of the application of the law on grounding authority decisions.
Keywords: Társadalomtudományok; Jogtudomány